The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40814-021-00791-6
|View full text |Cite
|
Sign up to set email alerts
|

A study protocol for a multicenter randomized pilot trial of a dyadic, tailored, web-based, psychosocial, and physical activity self-management program (TEMPO) for men with prostate cancer and their caregivers

Abstract: Background Prostate cancer predisposes patients and caregivers to a wide range of complex physical and psychosocial challenges, and interventions must incorporate a wide range of self-management strategies to help patients and their caregivers effectively cope with cancer challenges. To palliate this need, our team recently developed and evaluated the initial acceptability of a dyadic, Tailored, wEb-based, psychosocial, and physical activity self-Management PrOgram (TEMPO). TEMPO is a 10-week, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
3
0
1
Order By: Relevance
“…However, there were no other significant differences observed ‘TEMPO’ Prostate Cancer (couples-only) Web-based 10 weeks Self-Management, Communication, Lifestyle/ Behavioural Change, Psychoeducation, Symptom Management A study protocol for a multicenter randomized pilot trial of a dyadic, tailored, web-based, psychosocial, and physical activity self-management program (TEMPO) for men with prostate cancer and their caregivers Study Protocol (Lambert et al . [ 55 ] , Canada) N/A N/A Patient Information Leaflet Abdominal Cancer (Colorectal/ Ovarian) Paper-based 1–2 weeks prior to surgery Physical Activity, Nutrition, Relaxation, Smoking Cessation, Alcohol Cessation Prehabilitation in cancer care: patients’ ability to prepare for major abdominal surgery Original Article (Beck et al . [ 20 ] , Denmark) Qualitative interviews and adherence records The authors concluded from the combined adherence and interview data that the leaflet functioned as a tool to motivate and support patients’ prehabilitation-related actions WEST Breast Cancer Web-based 24 weeks Physical Activity, Nutrition, Telephone Counselling Effects of a web-based expert support self-management program (WEST) for women with breast cancer: A randomized controlled trial RCT (Kim & Kim [ 56 ] , Korea) HS-SES, Physical measures (e.g., height, weight) At 24 weeks, the intervention group demonstrated greater decreases in body fat/percentage and waist circumference but no differences were found for perceived self-efficacy WSEDI Breast Cancer Web-based 12 weeks Physical Activity, Nutrition, Self-Management Skills A Web-based self-management exercise and diet intervention for breast cancer survivors: Pilot randomized controlled trial ...…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no other significant differences observed ‘TEMPO’ Prostate Cancer (couples-only) Web-based 10 weeks Self-Management, Communication, Lifestyle/ Behavioural Change, Psychoeducation, Symptom Management A study protocol for a multicenter randomized pilot trial of a dyadic, tailored, web-based, psychosocial, and physical activity self-management program (TEMPO) for men with prostate cancer and their caregivers Study Protocol (Lambert et al . [ 55 ] , Canada) N/A N/A Patient Information Leaflet Abdominal Cancer (Colorectal/ Ovarian) Paper-based 1–2 weeks prior to surgery Physical Activity, Nutrition, Relaxation, Smoking Cessation, Alcohol Cessation Prehabilitation in cancer care: patients’ ability to prepare for major abdominal surgery Original Article (Beck et al . [ 20 ] , Denmark) Qualitative interviews and adherence records The authors concluded from the combined adherence and interview data that the leaflet functioned as a tool to motivate and support patients’ prehabilitation-related actions WEST Breast Cancer Web-based 24 weeks Physical Activity, Nutrition, Telephone Counselling Effects of a web-based expert support self-management program (WEST) for women with breast cancer: A randomized controlled trial RCT (Kim & Kim [ 56 ] , Korea) HS-SES, Physical measures (e.g., height, weight) At 24 weeks, the intervention group demonstrated greater decreases in body fat/percentage and waist circumference but no differences were found for perceived self-efficacy WSEDI Breast Cancer Web-based 12 weeks Physical Activity, Nutrition, Self-Management Skills A Web-based self-management exercise and diet intervention for breast cancer survivors: Pilot randomized controlled trial ...…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, use of problem‐focused coping, theoretically considered to be protective of anxiety (Lambert et al., 2021), may be more or less effective depending on the cause of dependency of care and condition (Wartella et al., 2009). Despite being informative however, our results should be interpreted with caution given that the number of studies included in our meta‐analyses comparing different caregiving groups was generally small.…”
Section: Discussionmentioning
confidence: 99%
“…The next step in evaluating TEMPO is a pilot study whereby a priori criteria have been established (see Table 2 ) to determine TEMPO ’s feasibility and acceptability. The objectives of this pilot randomized controlled trial (RCT) were to (a) examine its feasibility, which includes rates of recruitment and refusal, questionnaire completion (including questionnaires for future cost-utility analysis), and protocol infringement; (b) examine the acceptability of TEMPO as evidenced by attrition, adherence, satisfaction, and perceived usefulness; and (c) estimate the clinical significance on anxiety and quality of life (primary outcomes, Supplementary Material S2 ), as well as depression, self-management skills, physical activity, self-efficacy, and appraisal (secondary outcomes) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%